1995
DOI: 10.1021/ma00113a018
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Blends of Linear and Long-Chain-Branched Polyethylenes in the Solid State: A Study by SANS, SAXS, and DSC

Abstract: Differential scanning calorimetry (DSC), small-angle neutron scattering (SANS), and X-ray scattering (SAXS) have been used to investigate the solid-state morphology of blends of linear (high density) and long-chain-branched (low-density) polyethylenes (HDPE/LDPE). The blends are homogeneous in the melt, as previously demonstrated by SANS using the contrast obtained by deuterating the linear polymer. However, due to the structural and melting point differences (~20 °C) between HDPE and LDPE, the components may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 12 publications
6
71
0
Order By: Relevance
“…41 For a PVDF/PHB blend, it was concluded that existing spherulites of PVDF nucleate PHB crystallization and such ILC. 16 Cocrystallization may occur in blends of polymers, which contain chemically identical monomer units as in LDPE/HDPE blends 54,55 or in blends of copolymers, which are in part built up by identical monomer units (PVDF/PTrFE 57 ). Cocrystallization has also been found in blends of deuterated and protonated PE.…”
Section: Htc/ncc Systems: Crystallization Induced Composition Changesmentioning
confidence: 99%
“…41 For a PVDF/PHB blend, it was concluded that existing spherulites of PVDF nucleate PHB crystallization and such ILC. 16 Cocrystallization may occur in blends of polymers, which contain chemically identical monomer units as in LDPE/HDPE blends 54,55 or in blends of copolymers, which are in part built up by identical monomer units (PVDF/PTrFE 57 ). Cocrystallization has also been found in blends of deuterated and protonated PE.…”
Section: Htc/ncc Systems: Crystallization Induced Composition Changesmentioning
confidence: 99%
“…Although such binary blends of crystallizable polymers are very rare, these blends can be divided into three main categories. These are (i) polymer/low molecular weight diluents, such as PCL/ Trioxane mixture 1 3; (ii) blends of chemically similar species, such as blends of two poly(aryl ether ketones), 14 blends of two polyethylenes, 15 • 42 -44 homopolymer/segmented block copolymer, 16 • 17 copolymers of vinylidene fluoride/trifluoroethylene, 18 vinylidene fluoride-co-tetrafl uoroethy lene /vi ny lidene fluoride-co-hexafl uoroacetone19; (iii) two polymers of chemically different structures, such as PCL/poly(vinylidene chloride), 20 · 21 PHB/poly(ethylene oxide) (PEO), 22 and poly(butylene adipate) (PBA)/PVDF. 10 - 12 The blends in category (ii) form cocrystals in a certain crystallization conditions, however, the blends in category (iii) form segregated crystals.…”
mentioning
confidence: 99%
“…This is the usual behavior, as it is well known that LDPE and HDPE form homogeneous materials in the melt but only co-crystallize under certain conditions, depending on the composition of the mixture and the cooling rate (Wignall et al, 1995). At high cooling rates, the co-crystallization has been demonstrated (Fonseca and Harrison, 1998); however, when the melt is solidified at low or moderate cooling rates, as in our case, a blend of the two polymers, with two defined melting peaks, is obtained.…”
Section: Characterization Of the Waste Plastics And Their Blendsmentioning
confidence: 97%